2019
DOI: 10.1371/journal.pntd.0007290
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of P. vivax and P. ovale foci of infection in asymptomatic and symptomatic children in Northern Namibia

Abstract: Background Knowledge of the foci of Plasmodium species infections is critical for a country with an elimination agenda. Namibia is targeting malaria elimination by 2020. To support decision making regarding targeted intervention, we examined for the first time, the foci of Plasmodium species infections and regional prevalence in northern Namibia, using nested and quantitative polymerase chain reaction (PCR) methods. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…by Sutherland et al 25 , and 2020. The majority of included studies (14/36, 38.9%) were conducted in African countries (1 in Angola 9 , 1 in Equatorial Guinea 26 , 2 in Ethiopia 5 , 8 , 2 in Gabon 43 , 51 , 1 in Ghana 15 , 1 in Kenya 46 , 1 in Namibia 44 , 2 in the Republic of Congo/Congo 26 , 42 , 2 in Senegal 6 , 7 and 1 in Uganda 26 ), Asian countries (9 in China 12 , 14 , 32 , 35 , 39 , 49 , 50 , 52 , 53 , 2 in India 10 , 11 , 1 in Bangladesh 41 , 1 in Myanmar 12 and 1 in Thailand 13 ), Europe (3 in Italy 29 31 , 2 in France 23 , 45 , 2 in Spain 47 , 48 , 2 in the United Kingdom 25 , 34 and 1 in Germany 40 ) and Northern America (1 in Canada 28 ). Most of the included studies 23 , 25 , 28 , 30 – 32 , 34 , 35 , 39 , 40 , 45 , 47 – 50 , 52 , 53 (19/36, 52.8%) reported indigenous cases of malaria caused by P. ovale curtisi or P. ovale wallikeri , and the remaining studies (17/36, 47.2%) reported imported cases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…by Sutherland et al 25 , and 2020. The majority of included studies (14/36, 38.9%) were conducted in African countries (1 in Angola 9 , 1 in Equatorial Guinea 26 , 2 in Ethiopia 5 , 8 , 2 in Gabon 43 , 51 , 1 in Ghana 15 , 1 in Kenya 46 , 1 in Namibia 44 , 2 in the Republic of Congo/Congo 26 , 42 , 2 in Senegal 6 , 7 and 1 in Uganda 26 ), Asian countries (9 in China 12 , 14 , 32 , 35 , 39 , 49 , 50 , 52 , 53 , 2 in India 10 , 11 , 1 in Bangladesh 41 , 1 in Myanmar 12 and 1 in Thailand 13 ), Europe (3 in Italy 29 31 , 2 in France 23 , 45 , 2 in Spain 47 , 48 , 2 in the United Kingdom 25 , 34 and 1 in Germany 40 ) and Northern America (1 in Canada 28 ). Most of the included studies 23 , 25 , 28 , 30 – 32 , 34 , 35 , 39 , 40 , 45 , 47 – 50 , 52 , 53 (19/36, 52.8%) reported indigenous cases of malaria caused by P. ovale curtisi or P. ovale wallikeri , and the remaining studies (17/36, 47.2%) reported imported cases.…”
Section: Resultsmentioning
confidence: 99%
“…The first identification of the species P. ovale wallikeri and P. ovale curtisi was reported by Sutherland et al 25 . Since then, differences in morphology, clinical characteristics, laboratory parameters and genetic differences between the two species have been observed in Africa 5 9 , 15 , 26 , 42 44 , 46 , 51 , Asia 10 – 14 , 32 , 35 , 39 , 41 , 49 , 50 , 52 , 53 , Europe 23 , 25 , 29 31 , 34 , 40 , 45 , 47 , 48 , and North America 28 . This widespread distribution of P. ovale spp.…”
Section: Discussionmentioning
confidence: 99%
“…Of the five species of Plasmodia generally accepted to exploit humans for schizogony (Antinori et al, 2012), the three most predominant in Africa have been found in Botswana: P. falciparum, P. vivax and P. malariae (Motshoge et al, 2016). Given the presence of P. vivax, a small reservoir of P. ovale is also likely, and has been found in surrounding countries (Amanfo et al, 2016;Haiyambo et al, 2019;Ukpe, 1998;Wolfe, 1968). Here we discuss two of these species, P. falciparum and P. vivax, due to their prevalence, prognosis, and inclusion in malaria treatment guidelines in Botswana (Republic of Botswana, 2015).…”
Section: Malaria Parasites Found In Botswanamentioning
confidence: 99%
“…Details of the amplification reactions and cycling parameters for qPCR and nested PCR have been published previously. 25 …”
Section: Methodsmentioning
confidence: 99%
“…Details of the amplification reactions and cycling parameters for qPCR and nested PCR have been published previously. 25 Statistical analysis. Data were entered in an Excel (Microsoft, Redmond, WA) data sheet.…”
Section: Blood Sample Collection and Baseline Demographicsmentioning
confidence: 99%